Položaj priseljencev in potomcev priseljencev z območja nekdanje Jugoslavije na trgu dela v Sloveniji - Medvešek, Mojca (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2009)
THE INTEGRATION OF IMMIGRANTS AND DESCENDANTS OF IMMIGRANTS FROM THE TERRITORYOF FORMER YUGOSLAVIA IN THE LABOUR MARKET IN SLOVENIA. The article deals with the situation of immigrants from the former Yugoslavia and their descendants in the labour market in Slovenia. Differences between immigrants, descendants of immigrants and the majority population are highlighted through the presentation of statistical and other data, obtained by various empirical studies. In exploring the causes of the recorded differences between the studied populations, the authors focus in particular on three factors: discrimination on grounds of ethnicity, social and cultural capital. The results of their studies suggest that immigrants and their descendants experience above all the kind of discrimination on grounds of ethnicity that permeates interpersonal relations in workplaces and that is frequently the result of stereotypes and prejudices. In addition, the significant differences among ethnic groups in comparison with minor differences between immigrants and their descendants suggest that ethnicity is an important factor of social stratification in the Slovenian society.
Keywords: imigranti; Slovenia; Slovenija; potomci; etnične skupine; integracija; trg dela; socialni kapital; kulturni kapital; diskriminacija